Risk and Control Rights-Oriented Payment Method Selection for the Operation and Maintenance Phase of Public–Private Partnership Projects - Yubo Guo; Qian Zhang; Xianhao Li; Xin Wen; Wenting Zhan; Chuan Chen (Buildings, 2026)
Payment method selection for the Operation and Maintenance (O&M) phase of Public–Private Partnership (PPP) projects remains underexplored, despite its critical role in balancing risk and project control. Drawing on the theories of risk allocation and project control rights, this paper developed a theoretical model for payment method selection of the O&M phase of PPP projects through literature review; 13 influencing factors associated with the model were verified by interview. A survey of PPP professionals in China was analyzed to group these factors into four categories: maturity of pre-project work (MPPW), capacity of potential investors (CPIN), operating cost risk (OCRI), and capacity of local government (CLGO). The findings also reveal two distinct influencing mechanisms: the Cost-Plus-Fee (CPF) approach is preferred when MPPW, CLGO, and OCRI are high, but CPIN is low. Conversely, the Fixed-Price (FP) approach is favored when these factors are reversed. This study advances PPP financing and governance literature by integrating risk allocation and project control rights theories into a novel framework, enhancing the understanding of payment method selection in complex contexts. Besides, unpacking the influence mechanisms provides practitioners with a structured approach to better understand the determinants of payment method selection, thereby supporting more informed risk management, control allocation, and project outcomes in real-world settings.